Remediation of petroleum hydrocarbon contaminated soils using microwave processing systems - Tang'an, Diret Bitrus (2024)
The rise in the world’s energy demand has led to an increase in oil and gas exploitation and exploration activities. During these processes, spillages from crude oil and its refined products occur, resulting in major environmental problems such as land pollution. In Nigeria’s Niger Delta, Total Petroleum Hydrocarbons (TPH) is identified as a key land contaminant from these spillages that has led to the destruction of vegetation, posing severe health risks to the local population. This research carried out a robust and systematic technology evaluation for removing TPH from the contaminated soils.